2012
DOI: 10.1121/1.3664100
|View full text |Cite
|
Sign up to set email alerts
|

Underwater radiated noise from modern commercial ships

Abstract: Underwater radiated noise measurements for seven types of modern commercial ships during normal operating conditions are presented. Calibrated acoustic data (<1000 Hz) from an autonomous seafloor-mounted acoustic recorder were combined with ship passage information from the Automatic Identification System. This approach allowed for detailed measurements (i.e., source level, sound exposure level, and transmission range) on ships of opportunity. A key result was different acoustic levels and spectral shapes obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
242
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(256 citation statements)
references
References 32 publications
(51 reference statements)
9
242
2
3
Order By: Relevance
“…The sound spectrum showed to 100Hz, and above 100Hz sound levels decrease, which is a typical feature revealed in previous observations (e.g. Ross, 1976;McKenna et al, 2012). The peak of sound source 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 level occurred at~50Hz and they are~185dB,~183dB and~173dB depending on the lengths and operational speeds of the ship.…”
Section: Shipping Datasupporting
confidence: 82%
See 1 more Smart Citation
“…The sound spectrum showed to 100Hz, and above 100Hz sound levels decrease, which is a typical feature revealed in previous observations (e.g. Ross, 1976;McKenna et al, 2012). The peak of sound source 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 level occurred at~50Hz and they are~185dB,~183dB and~173dB depending on the lengths and operational speeds of the ship.…”
Section: Shipping Datasupporting
confidence: 82%
“…The source depth (SD) for all calculations is deployed at 7m, a typical depth of ship propellers (McKenna, et al, 2012). Accordingly, the RL at 1/3 octave central frequencies can be obtained using this equation.…”
Section: Sound Exposure Level Of Shipsmentioning
confidence: 99%
“…통과하는 선박의 방사소음레벨을 측정하였다 [9] . 보이는 것을 볼 수 있다 [10] . 이 결과는 본 시뮬레이터 를 활용하여 분석한 간섭패턴의 발생원인 분석과도 일 치하는 결과이다.…”
Section: 장에서는unclassified
“…The average annual growth rate between 2005 and 2015 was then computed for each segment to make a forward projection of the number of ships per segment in 2030. The average source level for each of these ship types was computed (on the linear scale) based on data contained in McKenna et al (2012) and was found to be 185.6, 181.0 and 185.7 dB re 1 Pa @ 1 m for container ships, oil tankers, and bulk carriers respectively. These data were selected because they are based on relatively new ships and represent values that are lower than those presented in earlier estimates (e.g., Arveson and Vendittis, 2000), thus adding a degree of conservatism to these projections.…”
Section: Methodsmentioning
confidence: 99%
“…Using that distance, the segment-wide sound exposure level (dB re 1 Pa 2 · h) was calculated using average speeds of 21.3, 13.3, and 14.1 knots for container ships, tankers, and bulk carriers respectively (McKenna et al, 2012) with the average source levels noted above and using the equation Projections for the number of ships in the global container, tanker and bulk carrier fleets in 2030, based on the growth rates for each segment over the last decade, suggest that the container and bulk carrier fleets will double over about the next 15 years, while the tanker fleet will undergo a more limited increase (Table 6.1); on average, these 3 segments will contribute to an 87% increase in ocean noise at the source. Based on these calculations, and assuming no change to the size of ships or their noise characteristics, the growth in fleet size in container ships and bulk carriers would result in more than a doubling in the source levels of these segments.…”
Section: Methodsmentioning
confidence: 99%